A Struggle for Survival: Meaning of Late Life in a Rural District in Uganda: A Qualitative Study - Knizek, Birthe Loa; Vancampfort, Davy; Kwiringira, Japheth; Kyazike, Elizabeth; Mugisha, James (Frontiers in Psychology, 2021)
Background: Uganda's ageing population (age 50 years and older) will nearly double from 2015 to 2050. Later life issues are therefore an area of increasing research and policy interest. This study aimed at exploring how ageing people in extreme poverty in a low-income country experience their everyday and what kind of meaning systems they employ in order to understand and cope with their living conditions affected by HIV and poverty in their late life. Methods: Qualitative interview of 14 participants in Buikwe district. We interviewed 11 women and 3 men and employed thematic analysis for the processing and analysis of the data. Results: Unanimously, all participants reported extreme poverty. The key informants emphasized respect from descendants and the community as a foundation for a meaningful later life. In contrast, only one care-receiver and no caregivers ever mentioned this aspect. The willingness/ability of the children to support the elderly in need of support constituted a big part of the care-receivers’ reflections as this was decisive for their position in society and the respect they would receive. In addition, both Christianity and traditional believes, as well as believes in witchcraft and ancestral spirits were employed as a basis for actions and reflections. Discussion: In conditions with extreme poverty, the question arises, whether life can be perceived as meaningful. Respect was mentioned as fundamental by the key informants, thereby giving priority to social relations as the most meaningful factor for living a meaningful life. The care-receivers’ focus on the ability and willingness of possible descendants to support might be a more down-to-earth description of this aspect, but without using the same level of abstraction. For the majority, their belief system did not serve as a source of consolation and their main focus was on social relationships for support. In order to improve the well-being of the old people their sense of meaning must be re-installed through a system guaranteeing the coverage of basic needs and measures to reinstall dignity through reintegration in both community and congregations. Social service agencies targeting elderly people need to work towards this objective.